PERCEPCIONES PROFESIONALES Y MOTIVACIONES PARA EL ACCESO A LA FORMACIÓN PERIODÍSTICA. EL CASO DE LOS ESTUDIANTES DE PERIODISMO DE LA UNIVERSIDAD COMPLUTENSE DE MADRID1 - Dra. Miriam Rodríguez Pallares,Dra. Dolores Rodríguez Barba,Dra. María José Pérez Serrano (Fonseca, Journal of Communication, 2023)
In the academic year 2013-2014, the MediaCom UCM research group conducted a study among students in the first and fourth year of the Degree in Journalism at UCM with the pretention to know the reasons that they decided to pursue these studies, their perceptions of journalism and media influence. From a quantitative analysis model relatively vocational criteria among students are perceived; generally they believe that journalists are not very independent and that political and economic factors influence in the activity of the media sector, whose influence on policy choices and consumption is subject to debate.